Role of nondrug methods in a package of measures for the prevention and treatment of osteoporosis: A review of literature - N. G. Badalov; T. V. Konchugova; L. A. Marchenkova; A. L. Persiyanova-Dubrova; E. Yu. Martynova (Современная ревматология)
The review represents the results of investigations into the role of nondrug methods in the treatment and prevention of osteoporosis (OA). The data available in the literature suggest that a number of non-drug technologies, first of all exercise therapy, aquatic therapy, reflexotherapy, electrical stimulation, and electromagnetic therapy, have proven efficiency and a certain potential for reducing the risk of osteoporosis and its complications and for improving bone metabolism. Expanding the range of these methods and increasing their validity for clinical introduction are very promising.